Genotoxic effects of (-)-cubebin in somatic cells of mice - Maistro, Edson Luis [UNESP]; Marcondes Natel, Andre Vinicius [UNESP]; Bianco de Souza, Gustavo Henrique; Perazzo, Fabio Ferreira (Wiley-Blackwell, 2011)
(-)-Cubebin belongs to the dibenzylbutyrolactone lignan group, which is widely distributed in the plant kingdom. Because this compound shows interesting biological activities, it is extremely important to evaluate its possible genotoxic activity to allow its safe use in humans. Thus, the present study was performed to investigate the genotoxicity potential activity of (-)-cubebin assessed by two assays: micronucleus in bone marrow cells and comet test in peripheral blood leukocytes of Swiss mice. In the (-)-cubebin dose range-finding assays, the maximum tolerated dose was greater than 2000 mg kg(-1). The compound was administered by an oral route at single doses of 250, 500 and 2000 mg kg(-1) body weight. Cytotoxicity was assessed by scoring 200 consecutive total polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCE/NCE ratio). Under our experimental conditions, micronucleus and comet assays, respectively, showed that (-)-cubebin caused dose-related clastogenic and genotoxic effects in the somatic cells investigated. PCE/NCE ratio showed no cytotoxicity for the three doses of the compound. The data suggest caution in the ingestion of (-)-cubebin by humans, especially at high doses. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: (-)-cubebin; micronucleus test; comet assay; clastogenicity; Piper cubeba